Factors influencing the internal party democracy of the All-Progressive Congress (APC) in the 2018 Kaduna State primary election, Nigeria - Adnan, Zatul Himmah; Ahmad, Zaid; Mohammed, Abubakar; Jawan, Jayum (Faculty of Human Ecology, Universiti Putra Malaysia, 2024)
The Progressive Congress (APC) internal party democracy (IPD) in Kaduna state was contested, particularly because the process of conducting the 2018 primaries is considered ineffective and inadequate. The process was accused of irregularities that led to bedevilled crises in the party in varying proportions, ranging from distrust among members, instability of the democracy, political thuggery, inter-party defections, anti-party politics, verbal warfare, and physical violence. This paper aims to explore the factors that influenced the conduct of the 2018 primary elections of the APC, which implies the various steps involved in the nomination of party flag bears or the party candidates for the general election. This paper was part of a study on the party's IPD during the 2018 Primary Election in Kaduna State, Nigeria. The data collection was based on one-to-one interviews with 18 informants selected from five distinct groups: party officials, ad-hoc delegates, politicians, rank-file members, and political analysts. In brief, the study found that personal interest, incumbency, incentives, and candidate selection methods as factors that influenced the conduct of the APC 2018 primary elections in Kaduna state. The study shows that the morals and integrity of the political actors affected the reputation of the party during the 2018 primary election. Based on this, it is pertinent that party stakeholders should shun all forms of interest and be committed to the implementation of internal party democratic doctrines in the conduct of party politics as a prerequisite for political party prosperity, democratic sustainability as well as democratic consolidation in Nigeria.